Association of community-level food insecurity and glycemic control among pregnant individuals with pregestational diabetes. Issue 1 (February 2023) - Venkatesh, Kartik K.; Joseph, Joshua J.; Clark, Aaron; Gabbe, Steven G.; Landon, Mark B.; Thung, Stephen F.; Yee, Lynn M.; Lynch, Courtney D.; Grobman, William A.; Walker, Daniel M.
Abstract: Aim: To evaluate whether pregnant individuals with pregestational diabetes who live in a food-insecure community have worse glycemic control compared to those who do not live in a food-insecure community. Methods: A retrospective analysis of pregnant individuals with pregestational diabetes enrolled in a multidisciplinary prenatal and diabetes care program. The exposure was community-level food insecurity per the Food Access Research Atlas . The outcomes were hemoglobin A1c (A1c) < 6.0 % in early and late pregnancy, and an absolute decrease in A1c ≥ 2.0 % and mean change in A1c across pregnancy. Results: Among 418 assessed pregnant individuals with pregestational diabetes, those living in a food-insecure community were less likely to have an A1c < 6.0 % in early pregnancy compared to those living in a community without food insecurity [16 % vs. 30 %; adjusted risk ratio (aRR): 0.55; 95 % CI: 0.33–0.92]. Individuals living in a food-insecure community were more likely to achieve a decrease in A1c ≥ 2.0 % [35 % vs. 21 %; aRR: 1.55; 95 % CI: 1.06–2.28] and a larger mean decrease in A1c across pregnancy [mean: 1.46 vs. 1.00; adjusted beta: 0.47; 95 % CI: 0.06–0.87)]. Conclusions: Pregnant individuals with pregestational diabetes who lived in a food-insecure community were less likely to enter pregnancy with glycemic control, but were more likely to have a reduction in A1c and achieve similar A1c status compared to those who lived in a community without food insecurity. Whether interventions that address food insecurity improve glycemic control and consequent perinatal outcomes remains to be studied. Highlights: Community-level food insecurity increased the risk of not achieving glycemic control in early pregnancy. Food insecurity impacts glycemic control among pregnant individuals with diabetes. Interventions targeting food insecurity to improve glycemic control and perinatal outcomes are needed.